Investigação de parasitoses e/ou comensais intestinais em manipuladores de alimentos de escolas públicas - da Silva, Eder Jose; Goncalves da Silva, Regildo Marcio [UNESP]; Silva, Luciana Pereira [UNESP] (Universidade Federal de Uberlândia (UFU), 2009)
The objective of this work was to identify intestinal parasites and/or commensals among food handlers of public schools in the city of Patos of Minas (MG). The fecal samples were analyzed by Lutz's method (1919). The positive results were 21.7% (13 cases) for parasites and/or commensal. The frequence of intestinal parasites and/or commensal of food handlers in the public schools showed low positive, probably as a result of good habits of personal hygiene and prophylactic treatment of parasitic.

Este trabalho objetivou investigar parasito e/ou comensais intestinais entre manipuladores de alimentos escolares no município de Patos de Minas. As amostras de fezes foram analisadas pelo método de Lutz. A positividade foi de 20% (12) para parasitos e/ou comensais intestinais. A prevalência de parasitos e/ou comensais intestinais foram baixos na população estudada em conseqüência de bons hábitos de higiene e tratamento profilático de parasitoses regularmente acompanhadas pelo clínico médico.
Investigation of intestinal parasites and/or commensals in food handlers of public schools
Keywords: Intestinal Parasites; Commensal; Food handlers